Respuesta :

Julik
3(4x+2) - 6x = 5x - 5(2 + x)
3·4x+3·2-6x=5x-5·2-5·x
12x+6-6x=5x-10-5x
12x-6x-5x+5x= -10-6
6x=-16
[tex]x=- \frac{16}{6} \\ x=- \frac{8}{3} \\ x=-2 \frac{2}{3} [/tex]

3(4x + 2) - 6x = 5x - 5(2 + x)

First, expand the equation. / Your problem should look like: 12x + 6 - 6x = 5x - 10 - 5x
Second, simplify 12x + 6 - 6x to 6x + 6. / Your problem should look like: 6x + 6 = 5x - 10 - 5x
Third, simplify 5x - 10 - 5x to -10. / Your problem should look like: 6x + 6 = -10
Fourth, subtract 6 from both sides. / Your problem should look like: 6x = -10 - 6
Fifth, simplify -10 - 6 to -16. / Your problem should look like: 6x = -16
Sixth, divide both sides by 6. / Your problem should look like: x = [tex] -\frac{16}{6} [/tex]
Seventh, simplify [tex] \frac{16}{6} [/tex] to [tex] \frac{8}{3} [/tex] / Your problem should look like: x = [tex]- \frac{8}{3} [/tex]

Answer: x = [tex]- \frac{8}{3} [/tex]

ACCESS MORE